Toward Climate-Resilient Hydropower in South Asia - Karki, Pravin (World Bank, Washington, DC, 2016)
The decision tree offers a cost effective, scientifically sound, replicable, and transparent method for demonstrating the robustness of a development project in the face of the risks posed by climate change, natural hazards, and other factors. The framework is most effective when a wide range of risks must be considered, as is typically the case with high-value hydropower investments. In order to gain maximum benefit from the framework, it should be conducted at both project and basin scale, first to answer questions immediately relevant to investors and then to provide perspective on alternative investment portfolios that may yield greater returns.